A case report of POEMS syndrome with renal involvement as immunotactoid glomerulopathy. Issue 9 (March 2018) - Wang, Yan; Yan, Yu; Sui, Zhun; Dong, Bao; Zuo, Li
Abstract: Rationale: POEMS syndrome is a rare multi-system disorder, which sometimes involves the kidney. Immunotactoid glomerulopathy (ITG) is an uncommon glomerular disease resulted from deposits of immunoglobulins and its derivatives. ITG caused by POEMS syndrome is rarely reported. Patient concerns: A 63-year-old man was presented with acute kidney injury. In addition, it's found that he had abnormal serum free κ /λ ratio, polyneuropathy, Castleman's disease, organomegaly, endocrinopathy and skin changes. Diagnoses: POEMS syndrome was diagnosed, Renal biopsy revealed an ITG. Interventions: Dexamethasone and thalidomide were given, as well as hemodialysis and other supportive treatments. Outcomes: The patient's extrarenal manifestations improved gradually and his renal function also showed slight improvement. Lessons: ITG caused by POEMS syndrome is rare, however, it makes sense that the monoclonal proteins produced by the plasma cells could cause ITG. Chemotherapy similar to that employed in multiple myeloma may be beneficial for these patients.